Story And Character Education Early Childhood (The Story of Prophet Ibrahim In Surat As-Shaffat) - Khoirunnisa’, Lina (ACIECE, 2018)
Character Education is a process of transformation of the values of life, whether it is the value ofgood character or bad character values that otherwise would is grown in the behavior ofindividuals who will be united in him, to be characteristic of the individual. Character educationis built from an early age, where the child's development is very rapid. One way of instillingvalues of character education in early childhood is the story that contains elements method tobuild the value of the child's character. Many stories can be told to children, one of which is themethod of lifting the story revolves around the Islamic containing elements of the value ofcharacter education of children. Through library research methods, the authors analyzed thevalues of character education early childhood in the story of Abraham Abraham is written in theQur'an letter As-Shaffat In the story of Abraham, there are some characters that can be used asan example for character education, including religious values, democracy and hard work